Au–Pd Core–Shell Nanoparticles as Alcohol Oxidation Catalysts: Effect of Shape and Composition. Issue 10 (4th September 2013) - Cheong, Soshan; Graham, Leah; Brett, Gemma L.; Henning, Anna M.; Watt, John; Miedziak, Peter J.; Song, Minghui; Takeda, Yoshihiko; Taylor, Stuart H.; Tilley, Richard D.
<x xml:space="preserve">Abstract</x> The right combination: Shape and composition are two important factors governing the catalytic properties of bimetallic nanocatalysts. Combining gold and palladium in a Au‐core–Pd‐shell structure coupled with an icosahedral morphology is shown to maximize catalytic performance for the selective oxidation of the biorenewable sources glycerol and 1, 2‐propanediol to glyceric and lactic acids, respectively.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>